A comparative study of artificial intelligence in education psychology: the cases of Indonesia and Thailand - Utina, Sitriah Salim; Chusniyah, Tutut; Inseachiangmai, Jittakorn; Zahra, Gebi Angelina; Pambudi, Kukuh Setyo (Bulletin of Social Informatics Theory and Application, 2024)
Various applications of artificial intelligence (AI) are currently being developed to enhance and transform the educational experience. However, things like culture, society, and ethics may have an impact on how artificial intelligence is implemented in classrooms all around the world. This study aims to analyze the existing use of AI in education in two Southeast Asian nations, namely Indonesia and Thailand, and to compare those two environments in terms of their potential. Specifically, the research will focus on Indonesia. We gathered papers, publications, and websites from both countries in order to perform an in-depth analysis as part of a comprehensive literature study that we carried out. The ethical and social repercussions of using AI in education, the best practices and suggestions for using AI in education, the possibilities and problems presented by using AI in education, and the preparedness and obstructions presented by using AI in education. Our study demonstrates that there are parallels and variances between the perceptions and experiences of educators and students from the two nations about the use of AI in educational settings, and it also makes recommendations for future research and practice